1997
DOI: 10.1021/om9610298
|View full text |Cite
|
Sign up to set email alerts
|

Five-Coordinate Ruthenium(II) and Osmium(II) Boryl Complexes

Abstract: The five-coordinate ruthenium boryl complexes, Ru(BR2)Cl(CE)(PPh3)2 (E = O, BR2 = BO2C6H4 (1a); E = O, BR2 = BO2C10H6 (1b); E = O, BR2= B(NH)2C6H4 (1d); E = O, BR2 = B(NH)SC6H4 (1e); E = S, BR2 = BO2C6H4 (2a); E = S, BR2 = B(NH)SC6H4 (2e); E = N-p-tolyl, BR2 = BO2C6H4 (3a)), result from the reactions of RuHCl(CE)(PPh3)3 with the appropriate borane. Related osmium compounds, Os(BR2)Cl(CE)(PPh3)2 (E = O, BR2 = BO2C6H4 (4a); E = O, BR2 = BO2C6H3CH3 (4c); E = O, BR2 = B(NH)2C6H4 (4d); E = O, BR2 = B(NH)SC6H4 (4e);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
3
28
1
1
Order By: Relevance
“…The osmium-boryl bond length of 2.076(3) Å (Os−B2) compares well with those reported for other osmium-boryl derivatives 22. …”
supporting
confidence: 84%
“…The osmium-boryl bond length of 2.076(3) Å (Os−B2) compares well with those reported for other osmium-boryl derivatives 22. …”
supporting
confidence: 84%
“…A number of ruthenium-and osmium-boryl species have also been prepared from the reaction between the respective HBR 2 and either a ruthenium-hydride (eq 18) or phenyl-osmium complex (eq 19). 75 Studies involving early transition metal complexes with boranes have been reported to be independent of metal-boryl formation in catalytic processes and sometimes result in the formation of hydridoborate compounds. 47,50,54,[56][57][58][59][60][61] Hartwig and De Gala 47 reported that the reaction of [Cp 2 NbH 3 ] with catecholborane or 9-borabicyclononane (9-BBN) yielded 1 equiv of hydrogen gas as well as the metal-boryl compound, [Cp 2 NbH 2 (Bcat)], or the hydridoborate compound, [Cp 2 Nb{BH 2 (C 8 H 14 )} 2 ], respectively; the latter compound may not necessarily be formed via an oxidative addition mechanism.…”
Section: Reactions With Hydridoboranes (H−br 2 )mentioning
confidence: 99%
“…[13] An elegantly designed cryptand that is highly sensitive and selective for binding NH 4 has been reported. The ruthenium ± boron bond of 2.161(5) is without precedent for comparison, but falls within the range (2.046(7) ± 2.20(2) ) found in osmium ± s-boryl complexes, [8,9] which contain an OsÀB pbonding component, but none of the ring strain that must be accommodated in the tricyclic structure of 4. One of the three Ru À S bond lengths, the one that is trans to the carbonyl group (that is, adjacent to the bulky phosphane) is, as expected, significantly longer (2.4857 (14) ) than the pair of mutually trans RuÀS bonds (RuÀS(1) 2.4066(14), RuÀS(2) 2.4112 (14) ).…”
Section: }] (3)mentioning
confidence: 99%
“…In this context, the elegant synthesis of ruthenium ± sboryl complexes by Roper and Wright et al through the reactions of [Ru(C 6 H 5 )Cl(CO)(PPh 3 ) 2 ] with boranes [8,9] provides compelling support for the proposed mechanism. Dissociation of one mt arm followed by agostic B À H coordination and ultimate oxidative addition of the BÀH bond could provide a cis-hydrido ± vinyl complex that undergoes alkene reductive elimination with formation of 4.…”
Section: ) 2 ] (R Vinyl Aryl) With K[hb(pz) 3 ] Is Known To Provide mentioning
confidence: 99%